Combination of Acid and Base Activation of Montmorillonite Clay and Its Impact on the Basic Blue-41 Removal Properties: Regeneration and Single Batch Design - Thamer S. Alraddadi; Rawan Al-Faze; Saheed A. Popoola; Mohd Gulfam Alam; Souad Rakass; Hmoud Al Dmour; Fethi Kooli (Inorganics, 2025)
The treatment with an alkali (sodium hydroxide) solution of acid-activated montmorillonite clay minerals resulted in a reduction in specific surface area. However, a significant enhancement in the removal of basic blue-41 dye solution was achieved compared to acid-activated samples only (first step of activation) and to the raw montmorillonite clay. The obtained products were characterized using different techniques. The results indicated that the acid-activated montmorillonites exhibited different physicochemical properties than the starting raw montmorillonite, with a reduction in the cation exchange capacity and improvements in the specific surface area (from 5 m2/g to 274 m2/g) and total pore volume (from 0.031 cm3/g to 0.450 cm3/g) due to the formation of the amorphous silica phase. However, the treatment with NaOH solution was accompanied by significant reductions in the specific surface area (from 274 m2/g to 18 m2/g) and total pore volume (from 0.450 cm3/g to 0.02 cm3/g) due to the dissolution of the formed amorphous silica phase, as confirmed through 29Si MAS NMR and FTIR techniques. In addition, the SiO2/Al2O3 molar ratios were close to those of the starting montmorillonite clay. The removal of the cationic basic blue-41 was optimized under different conditions, such as different initial concentrations, adsorbent doses, and pHs of the dye solution. The maximum removal capacities of acid-activated clays were in the range of 45 mg/g to 80 mg/g and decreased with the extent of the acid activation process. However, the capacities were enhanced after NaOH treatment and reached values in the range of 80 to 120 mg/g. Enhancing the surface area had less of an impact on the materials’ removal ability. The obtained materials performed well in seven adsorption–regeneration cycles, showing a 70% reduction in removal effectiveness.